A STUDY ON THE FINANCIAL GROWTH OF COMPANIES DUE TO GREEN PROJECTS- REFERRING TO BUILDERS: AN ENVIRONMENTAL APPROACH - Maria Josephine Swathi; L. Augustin Amaladas (European Scientific Journal, ESJ, 2014)
Today our planet is in peril. Due to negligence of people, their greediness and selfish attitude has put earth in great danger. To fulfill their wants and needs people cut down trees, lay concrete roads, dig bore-wells, and destroy forests which are the major reason for natural calamities happening these days leading to threat to life in this planet. To overcome these problems there are various measures taken up by individuals, corporate, government and society. ―GREEN BULIDING‖ is one of the measures taken up mainly by the corporate sector. This paper brings out the importance of green building in the present scenario and explores the idea of green building/ green projects taken up by currently in the corporate field. This paper analyses the financial aspects of the companies taking up these projects and their growth and the companies backing out from these projects. Reason for choosing this topic is to highlight the financial growth of companies by taking these projects and motivating other companies to take up this challenge and change their negative attitude to make a choice in entering into such projects. This research also creates awareness in preservation of natural resources. Since green building is a live talk in the society made me to choose the topic, which will be tool in protecting the environment. The data required for the study have been collected from primary and various secondary sources. Green building concept in India is on the process of flourishment. Green building concept at present looks expensive but when compared the genies and benefits are higher. When green building concept flourishes the cost of the green building implementation will automatically reduce.